Protocol for a prospective multicentre registry cohort study on suicide attempters given the assertive case management intervention after admission to an emergency department in Japan: post-ACTION-J Study (PACS). Issue 9 (4th October 2018) - Kawanishi, Chiaki; Ishii, Takao; Yonemoto, Naohiro; Yamada, Mitsuhiko; Tachikawa, Hirokazu; Kishimoto, Toshifumi; Tsujii, Noa; Hashimoto, Satoshi; Kinoshita, Toshihiko; Mimura, Masaru; Okubo, Yoshiro; Otsuka, Kotaro; et al.
Abstract : Introduction: Suicide attempt is the most important risk factor for later suicide. A randomised-controlled, multicentre trial of postsuicide attempt case management for the prevention of further suicide attempts in Japan, named ACTION-J, has established effective interventions for prevention of suicide reattempts. The ACTION-J assertive case management intervention programme was adopted by the Japanese Ministry of Health, Labour and Welfare in 2016, when medical fees were revised. This nationwide programme is provided to patients who attempt suicide and who are admitted to emergency departments in Japan. The aim of the present study is to examine the current implementation status of the ACTION-J programme. The present study also aims to clarify which patients' and hospitals' factors affect the implementation of the programme. Methods and analysis: This is a prospective, multicentre, patient registry cohort study. Participants will be suicide attempters admitted to the emergency departments of medical facilities with both psychiatry and emergency departments. The assertive case management programme will be delivered to participants by a case manager for up to 24 weeks, based on psychiatric diagnoses, social risks and patient needs. The core feature of the programme is to encourage patients to participate in psychiatric treatment. The primary outcome will be the proportion of patients still participating in the case management intervention at 24 weeks after registration. The secondary outcomes will include measures of the fidelity of the case management intervention. The fidelity will be evaluated using a fidelity assessment manual developed by the study group. Ethics and dissemination: This observational study has been approved by the ethics board of Sapporo Medical University. Enrolment began in October 2016 and will continue until December 2018. Dissemination plans include presentations at scientific conferences and scientific publications. Trial registration: UMIN000024474.